Analysis of Abnormal Return and Trading Volume Activity on the Announcement of Danantara Holding in Conventional Banks Listed on the Indonesia Stock Exchange (IDX) - Fahimma Nur Aulia; Burhanudin (LP2M IAIN Palopo, 2026)
This study analyzes market reactions to the announcement of the Danantara Holding in conventional banks listed on the Indonesia Stock Exchange (IDX) using an event study methodology. Amidst the resilience of the Indonesian capital market in 2024 (IHSG: 7,036.57), the Danantara announcement on February 24, 2025, raises questions about the market's efficiency in absorbing structural policy information. The study aimed to examine the differences in Abnormal Return (AR) and Trading Volume Activity (TVA) before and after the announcement. This descriptive quantitative study used purposive sampling of 50 conventional banks, resulting in 12 samples (168 observations). Secondary data from the IDX, Yahoo Finance, and Investing.com were analyzed using a market-adjusted model, normality tests (Kolmogorov-Smirnov/Shapiro-Wilk), and the Wilcoxon Signed Rank Test using SPSS. The results show that the difference in AR is not significant (Sig. 0.827 > 0.05; mean: 0.0036 to -0.0005) but the increase in TVA is significantly positive (Sig. 0.000 < 0.05; mean: 0.0010 to 0.0016), rejecting both hypotheses. The findings confirm semi-strong market efficiency where structural policy information has been anticipated, consistent with the EMH and signaling theory.